2013
DOI: 10.1061/(asce)co.1943-7862.0000732
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Construction Safety and Quality Performance

Abstract: It is well established that the project cost, quality, safety, and duration are the four critical elements that contribute to project success. Past literature has established theoretical relationships between construction safety and quality on the basis of opinions of industry experts. This is the first empirical inquiry into the relationship between safety and quality, testing the null hypothesis that there is no statistical relationship among quality performance indicators and safety performance indicators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
101
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 35 publications
0
101
1
2
Order By: Relevance
“…Rework is an endemic problem in building projects, and can have an adverse impact on the performance (CII, 2001;Hwang et al, 2009;Love et al, 2009;Love et al 2010, Wanberg et al, 2013Love et al 2015) of construction and engineering projects. On average, rework contributes to 52% of the total cost growth that is incurred, and can increase the schedule overrun by 22% (Love, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Rework is an endemic problem in building projects, and can have an adverse impact on the performance (CII, 2001;Hwang et al, 2009;Love et al, 2009;Love et al 2010, Wanberg et al, 2013Love et al 2015) of construction and engineering projects. On average, rework contributes to 52% of the total cost growth that is incurred, and can increase the schedule overrun by 22% (Love, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies confirmed that there is a relation between quality and safety as work-related outcomes (Wanberg et al, 2013).…”
Section: Psychological Empowermentmentioning
confidence: 96%
“…Quality, in its simplest form, can be defined as: 'meeting the customer's expectations, ' or 'compliance with customer's specification [3]. In the literature review, it is found that the primary indicators of construction quality are percent cost of rework and rate of construction defects [4]. On the basis of a comprehensive literature review, the reported several measures of rework are errors, omissions, failures, damage, and change orders throughout the procurement process [5].…”
Section: Introductionmentioning
confidence: 99%